2022
DOI: 10.4018/ijesma.296576
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Customer Loyalty in the Mobile Banking Setting

Abstract: This study uses a novel theoretical approach that combines two multidimensional service quality models that focus on customer satisfaction, perceived value, and customer loyalty as outcomes of service quality in the context of mobile banking. Additionally, the study assesses the potential moderating effects of switching costs between mobile banking service quality and customer loyalty. The study found a strong direct effect between service quality, perceived value, customer satisfaction, and loyalty. The moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…In MB research, our findings are in line with recent studies' results (Bui et al, 2022;Poromatikul, et al, 2021), and provide additional insights about the direct impact of value perception on satisfaction, while this link has been indirect, via trust in the research of Berraies et al (2017).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In MB research, our findings are in line with recent studies' results (Bui et al, 2022;Poromatikul, et al, 2021), and provide additional insights about the direct impact of value perception on satisfaction, while this link has been indirect, via trust in the research of Berraies et al (2017).…”
Section: Discussionsupporting
confidence: 91%
“…Several authors have verified the direct impact in a traditional banking context (Omoregie et al, 2019) and mobile banking one (Poromatikul, et al, 2021). Consistent with these prior studies in the mobile banking environment (Bui et al, 2022;Poromatikul, et al, 2021), it is suggested that satisfaction is influenced by value. Accordingly, H10: In a mobile banking context, perceived value positively impacts consumer satisfaction.…”
Section: Relationship Between Perceived Value and Satisfactionsupporting
confidence: 77%
See 1 more Smart Citation
“…Service quality denotes the degree to which interaction with a mobile banking application matches customer needs. High service quality of mobile banking applications results in customers' satisfaction which in turn leads to their loyalty [15]. It is, therefore, of great importance that mobile banking applications meet customers' expectations and needs.…”
Section: Service Quality Of Mobile Banking Applicationsmentioning
confidence: 99%
“…Only two study participants have singled out the security of personal data as the strength of mobile banking applications. On the other hand, lack of relevant functionalities (15), security concerns (8), issues with responsiveness (7), difficulties in use (4), and various technical problems, including common updates (3), were recognized by clients of mobile banking applications as their biggest shortcomings.…”
Section: Pros and Cons Of Mobile Banking Applicationsmentioning
confidence: 99%